Chemical Analysis of Limestone of Bojhe, Halesi-Tuwachung Municipality, for Industrial Applications - Gharti, Ram Bahadur; Hitan, Dipak Kumar; Prasad, Manoj Kumar; Oli, Hari Bhakta (Amrit Research Journal, 2020)
Limestone is principal raw material for cement making industries. Chemical composition of limestone plays great role for making good quality cement. Production of good quality cement is of primary importance for the increment of the durability of infrastructure. Nepal is establishing large number of cement industries that uses limestone as raw materials and it is urgent to determine the quality of limestone. Quantitative Chemical analysis of one hundred forty three (143) limestone samples, collected by the channel sampling method, is carried out using gravimetric, titrimetric, and atomic absorption spectroscopic methods. The determined values of different parameters in percentages are as follows; loss on ignition (41.96385±0.670325), acid insoluble matter (2.412308±1.014588), Fe2O3 (0.263846±0.082249), Al2O3 (0.765385±1.656052), CaO (52.20538±1.656052) and MgO (3.018462±0.703886). The results indicated that most of the limestone samples are found to meet industrial raw material specifications for some industries. They can be used in the cement, agriculture (liming of soil and fish ponds) and metallurgical purification processes in the steel industry. Collected limestone samples meet the raw material specification of some industries. So establishment of such industries from a chemical point of view is feasible.